Comparison of Six Commercial Diagnostic Tests for the Detection of Dengue Virus Non-Structural-1 Antigen and IgM/IgG Antibodies - Lee, Hyeyoung; Ryu, Ji Hyeong; Park, Hye-Sun; Park, Ki Hyun; Bae, Hyunjoo; Yun, Sojeong; Choi, Ae-Ran; Cho, Sung-Yeon; Park, Chulmin; Lee, Dong-Gun; Lim, Jihyang; Lee, Jehoon; et al. (Annals of Laboratory Medicine, 2019)
ELISAs and rapid diagnostic tests (RDTs) are widely used for diagnosing dengue virus (DENV) infection. Using 138 single blood samples, we compared the ability to detect non-structural (NS)-1 antigen and anti-DENV IgM/IgG antibodies among (1) DENV Detect NS1 ELISA, DENV Detect IgM capture ELISA and DENV Detect IgG ELISA (InBios International, Inc.); (2) Anti-Dengue virus IgM Human ELISA and Anti-Dengue virus IgG Human ELISA (Abcam); (3) Dengue virus NS1 ELISA, Anti-Dengue virus ELISA (IgM) and Anti-Dengue virus ELISA (IgG) (Euroimmun); (4) Asan Easy Test Dengue NS1 Ag 100 and Asan Easy Test Dengue IgG/IgM (Asan Pharm); (5) SD BIOLINE Dengue Duo (Standard Diagnostics); and (6) Ichroma Dengue NS1 and Ichroma Dengue IgG/IgM (Boditech Med). For NS1 antigen detection, InBios and Euroimmun showed higher sensitivities (100%) than the RDTs (42.9-64.3%). All tests demonstrated variable sensitivities for IgM (38.1-90.5%) and IgG (65.7-100.0%). InBios and Boditech Med demonstrated higher sensitivity (95.6% and 88.2%, respectively) than the other tests for combined NS1 antigen and IgM antibody. Five NS1 antigen tests had good agreement (92.8-98.6%) without showing positivity for chikungunya. However, all IgG tests demonstrated potential false-positivity with variable ranges. Clinical laboratories should note performance variations across tests and potential cross-reactivity.